Increased sensitivity of a new commercial reverse transcriptase-quantitative PCR for the detection of Pneumocystis jirovecii in respiratory specimens. (13th May 2021) - Dellière, Sarah; Hamane, Samia; Aissaoui, Nesrine; Gits-Muselli, Maud; Bretagne, Stéphane; Alanio, Alexandre
Abstract: Optimal sensitivity to detect low Pneumocystis loads is of importance to take individual and collective measures to avoid evolution towards Pneumocystis pneumonia and outbreaks in immunocompromised patients. This study compares two qPCR procedures, a new automated RTqPCR using the GeneLEAD VIII extractor/thermocycler (GLVIII; ∼2.2 h workflow) and a previously validated in-house qPCR assays (IH; ∼5 h workflow) both targeting mtSSU and mtLSU for detecting P. jirovecii in 213 respiratory samples. GLVIII was found to be more sensitive than IH, detecting eight more specimens. Bland-Altman analysis between the two procedures showed a Cq bias of 1.17 ± 0.07 in favor of GLVIII. Lay Summary: The fungus Pneumocystis needs to be detected early in respiratory samples to prevent pneumonia in immunocompromised hosts. We evaluated a new commercial RTqPCR on 213 respiratory samples to detect Pneumocystis and found it more sensitive and faster than our routine sensitive in-house qPCR assay.